STUDI LITERATUR PEMBELAJARAN MEDIA GEOMETRI DALAM MENINGKATKAN KEMAMPUAN KOGNITIF ANAK USIA DINI DI TAMAN KANAK-KANAK - Indriana Warih Windasari; Agustiarini Eka Dheasari (Al-ATHFAL: Jurnal Pendidikan Anak, 2023)
Cognitive ability is one aspect that is very important to develop because children can think, understand, and explore the things that are around them. Through good cognitive abilities children can also solve all the problems they face, and it will be a provision for children as adults. One of the things that can be used to develop these abilities is through geometry media, where the media teaches various forms of basic patterns. Activities that can be done with geometry media include classifying, recognizing shapes, sizes, and patterns that can be applied in everyday life. This research uses the Literature Review method and is included in qualitative research, where researchers do not go to the field to collect data. The results showed: 1) Early childhood is a time when children are sensitive to various kinds of stimuli in their environment. High curiosity and developmental aspects that must be maximally improved need to be facilitated properly; 2) Children's cognitive abilities can be improved through the use of geometry media in classroom learning activities. Through a variety of games designed according to the needs of child development then cognitive abilities of children can develop well and maximally; 3) The use of geometry media in learning can develop children's cognitive abilities among them.